Defensive urbanism and local governance - Gema Varona (Oñati Socio-Legal Series)
In contrast with the perspective of local safety audits for women, which aim to promote the democratic use of public space in the context of inclusive urbanism or pro-social design, defensive urbanism is a term that has been related to situational prevention in order to bar or restrict the use of public space by several stigmatised groups. This trend can be understood in terms of the broken windows theory and zero tolerance approaches in criminology as well as of social exclusion in globalised cities. This paper will tackle the origin and development of the concept of defensive urbanism, as a kind of local governance related to broader trends in securatisation, as well as its visible ramifications in some administrative regulations in some Basque municipalities.